2009
DOI: 10.1113/expphysiol.2008.045732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic exercise on DNA fragmentation and on lipid profiles in rat skeletal muscle

Abstract: The concentration and fatty acid composition of phospholipids in animal cells are important determinants of membrane function. Membrane function may influence apoptosis, a biological process that is crucial for the normal development and function of the body. Few and conflicting data exist regarding the effect of chronic exercise on apoptosis in skeletal muscle, and no data exist regarding the effect of chronic exercise on the fatty acid composition of individual muscle phospholipids. We therefore examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The ceramide level does not change in the trained group although the activities of the key enzymes of ceramide metabolism changed. The data regarding the content of ceramide are in agreement with the results reported previously, where 8 week training did not affect the ceramide content in rat gastrocnemius muscle [44]. In human skeletal muscle, training did not change the total ceramide content [27].…”
Section: Discussionsupporting
confidence: 91%
“…The ceramide level does not change in the trained group although the activities of the key enzymes of ceramide metabolism changed. The data regarding the content of ceramide are in agreement with the results reported previously, where 8 week training did not affect the ceramide content in rat gastrocnemius muscle [44]. In human skeletal muscle, training did not change the total ceramide content [27].…”
Section: Discussionsupporting
confidence: 91%
“…sistent with these previous data, we observed a significant exercise training-dependent reduction in DNA fragmentation in soleus of hypertensive rats. Previous research in healthy rats found that regular exercise training nonsignificantly (33%; P ϭ 0.06) reduced skeletal muscle DNA fragmentation (60); however, not all reports support such reductions in healthy muscle (67). The level of DNA fragmentation is relatively low in healthy skeletal muscle (47); thus, further reductions may not be possible or may be below detectable limits.…”
Section: Discussionmentioning
confidence: 93%
“…During muscle contractions, plasma FAs are uptaken and/or stored in muscle cells as an important energy source, then lipolyzed to generate energy. Small changes in total lipid amounts with muscle contraction have been detected by conventional biochemical methods such as thin-layer chromatography, [4][5][6], suggesting that dynamic change in lipid composition, rather than lipid amount, occurs during muscle contraction. However, it is poorly understood what type of molecular species is changed by muscle contractions because a valid methodology has not been established.…”
Section: Introductionmentioning
confidence: 98%